(untitled) (Damascus University Journal for the economic and Political sciences, 2025)
The study aimed to determine the role of joint audit in enhancing the quality of the audit process, by clarifying the role of (contracting and engagement, cooperation and coordination, distribution and allocation of work) in enhancing the quality of auditing. The descriptive approach was relied upon by applying it to audit offices and companies subject to the supervision of the Securities Commission. A questionnaire was distributed to a sample of 80 companies and audit offices licensed in Iraq, and (78) valid questionnaires for statistical analysis were retrieved. The SPSS statistical program was relied upon to analyze the questionnaire, display descriptive statistics for the study variables based on arithmetic means and standard deviations, and test hypotheses using simple and multiple linear regression. The study found that there is a positive relationship with a moral significance between joint auditing and enhancing the quality of the audit process, through the presence of a positive relationship with a moral significance between (contracting and association, cooperation and coordination, and the distribution and allocation of work) and enhancing the quality of the audit process, in Iraqi audit offices and companies.